Employees’ Perception of Green Banking Practices in Nepal - Adhikari, Nabin Bahadur (Journal of Interdisciplinary Studies, 2024)
Green banking differs from traditional banking as it focuses on promoting environment-friendly banking. Nowadays, due to the huge deterioration of the environment, not only human beings but also the day-to-day business environment suffers adversely. The objective of this research paper is to assess employee perceptions towards green banking practices in Nepalese commercial banks. Furthermore, the paper aims to assess the mechanisms of green banking practices, to analyze the impact of banking activities on green banking practices, to analyze the relationship between banking activities and green banking practices, to analyze the significant difference between green banking practices and to assess the challenges of green banking practices in Nepal from the employees’ angle. This study used descriptive and casual comparative research design and it took a sample of 390 employees working in three sample commercial banks. The independent variables are operational activities; employee-related practices, customer-related practices and bank’s policy-related practice whereas the dependent variable is green banking practices. Based on the responses of employee, it is concluded that debit cards, mobile banking, credit cards, online banking, and electronic payment are common in Nepalese commercial banks. From the correlation and regression analysis, it was found that the independent variable has a positive significant relationship to the green banking practices. The practice of green banking is more or less similar among the sample banks and there is a lack of evidence of difference between gender and green banking practice in Nepal. Most of the employees of sample banks perceive that the major barrier for the effective practice of green banking is customers’ insufficient awareness. Hence the green banking practice is more or less compulsory for making their institution competitive so the apex body should formulate effective policies and customer and employees too aware immediately as soon as possible.